1969
DOI: 10.32473/edis-ag184-2003
|View full text |Cite
|
Sign up to set email alerts
|

Forage Soybeans for Grazing, Hay and Silage

Abstract: Livestock producers need a high-protein summer forage. Forage soybeans fit well in a production system following small grains or early planted corn. This document is SS-AGR-180, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised January 2003. SS-AGR-180/AG184: Forage Soybeans for Grazing, Hay, and Silage (ufl.edu)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Increasing protein content of feed used in rations of high-yield ruminants is a costly practice (Spanghero et al, 2015). Addition of legumes into maize silage increases not only the protein contents, but also the metabolisable energy, taste and the other quality parameters of the silage (Demirel et al, 2009;Blount et al, 2003). Therefore, maize is ensiled in mixtures with soybean (Kizilsimsek et al, 2017), climbing beans (Contreras-Govea et al, 2009), cowpea and bean (Geren et al, 2008), red clover and lupin (Carruthers et al, 2000) and alfalfa (Ozturk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing protein content of feed used in rations of high-yield ruminants is a costly practice (Spanghero et al, 2015). Addition of legumes into maize silage increases not only the protein contents, but also the metabolisable energy, taste and the other quality parameters of the silage (Demirel et al, 2009;Blount et al, 2003). Therefore, maize is ensiled in mixtures with soybean (Kizilsimsek et al, 2017), climbing beans (Contreras-Govea et al, 2009), cowpea and bean (Geren et al, 2008), red clover and lupin (Carruthers et al, 2000) and alfalfa (Ozturk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean is a good source of protein, fiber, micronutrients, vitamins, isoflavonoids and oil, which can be used in the food and biodiesel industries. In recent years, there has been a decrease in the value of soybean as oilseed, which has led to the enhancement of soybean cultivation for forage, providing high-quality grazing, hay or silage. , …”
Section: Introductionmentioning
confidence: 99%
“…The CP content of soybean silage was 15.56%, and the CP content of the silage increased as in soybean ratio increased in the mixture (p<0.05). Blaunt et al (2006) reported that the soybean supplement did not only increase the CP level in corn silage but also improved the taste and energy level. Demirel et al (2009) stated that a 20% or 30% soybean additive was required in addition to corn to increase the CP content in corn silage and to improve the fermentation of soybean.…”
Section: Chemical Composition and Silage Fermentation Characteristics Of Corn And Soybean Intercropping Systemsmentioning
confidence: 99%